An updated meta-analysis of TAVR in patients at intermediate risk for SAVR - Lazkani, Mohamad; Singh, Nirmal; Howe, Carol; Patel, Nachiket; Colón, Modesto J.; Tasset, Mark; Amabile, Orazio; Morris, Michael; Fang, H. Kenith; Pershad, Ashish (Cardiovascular revascularization medicine, 2019)
Transcatheter aortic valve replacement (TAVR) has been approved for use in patients with severe aortic stenosis at intermediate, high and extreme surgical risk. This meta-analysis was performed to assess the safety and efficacy of TAVR compared to surgical aortic valve replacement (SAVR) in intermediate risk patients. We searched PubMed, EMBASE, Web of science, and the Cochrane Central Register of Controlled Trials databases for studies comparing TAVR versus SAVR in patients at intermediate surgical risk, with a mean Society of Thoracic Surgeon score of 3–8% or a mean logistic European risk score of 10–20%. The primary endpoint was to assess the efficacy of TAVR compared to SAVR, defined as all-cause and cardiovascular mortality at 30-days, 1-year, and ≥2 years of follow-up. Secondary endpoints were the safety profile, comprising of cerebrovascular events, myocardial infarctions, permanent pacemaker placement, new onset atrial fibrillation, aortic regurgitation, vascular complications, major bleeding and acute kidney injury. This is the largest and most contemporary meta-analysis of 5647 intermediate risk patients in eleven studies published to date. There were no statistically significant differences in all-cause and cardiac mortality at 30 days, 1- year and >2-years of follow up. Acute kidney injury and atrial fibrillation occurred more frequently in patients treated with SAVR and permanent pacemaker implantation and aortic insufficiency were more frequent in patients treated with TAVR. This meta-analysis suggests that for intermediate risk patients with severe aortic stenosis, TAVR has similar efficacy as SAVR but with a different adverse event profile. •TAVR is as effective as SAVR with comparable safety in intermediate risk patients.•The incidence of kidney injury is lower with TAVR than with SAVR.•The incidence of postoperative atrial fibrillation is lower with TAVR than with SAVR•The incidence of paravalvular leak is higher with TAVR than with SAVR.•Higher pacemaker rates in intermediate risk patients should be considered with TAVR.